MENUJU KEBAHAGIAAN DAN PERSATUAN DENGAN ALLAH MELALUI METODE PENYERUAN NAMA ALLAH - Shelomita Selamat & Eleine Magdalena (Jurnal Alternatif Wacana Ilmiah Interkultural, 2022)
The calling of God's name in meditation is a Christian traditional spiritual wealth which can be practiced by all people who are seeking the inner solitude and silence. All means that have been known in traditions and religions which lead to God’s name as ultimate reality can be a medium towards the union of God. By calling God's name based on love and self-surrender, a person can reach the inner solitude in the union of God. The calling of God's name in meditation gives the interior transformation which gives effects for improving life quality from the five respondents in this research. The existential emptiness can only be filled by God and this can be reached by one's awareness on God's existence in the souls by calling His name in love.